ROBUST FRAMEWORK OF HALAL CERTIFICATION PROCESS WITH INTEGRATION OF ARTIFICIAL INTELLIGENT METHOD - Nashirah Abu Bakar; Sofian Rosbi (Journal of Islamic, Social, Economics and Development, 2019)
Halal status is main element of consideration for product consumption among Muslim consumers. However, the halal scientific detection method is still having many room for improvement to attaining better accuracy of halal certification. Therefore, the objective of this study is to evaluate the framework for Halal certification using scientific detection analysis with artificial intelligent method. This study introduced two methods for artificial intelligent namely genetic algorithm and neural networks. This paper is a conceptual paper which focuses on the halal food certification framework including halal certification management. The framework of reliable artificial intelligent system for halal monitoring involving three (3) elements for testing namely Halal Testing (HT), Safety Testing (ST) and Nutritional Testing (NT). The significant value of this study is it provides better understanding for public awareness regarding robust framework of halal certification process.